Toronto Math Forum
APM3462016F => APM346Lectures => Chapter 8 => Topic started by: Roro Sihui Yap on November 23, 2016, 12:36:48 AM

http://www.math.toronto.edu/courses/apm346h1/20169/PDEtextbook/Chapter8/S8.1.html#mjxeqneq8.1.15
Just below equation (15), I think that it should be
$$\frac{\rho^2 P''+2\rho P'+\lambda \rho^2 P}{P}+
\frac{\Lambda Y }{Y}=0$$
Instead of:
$$\frac{\rho^2 P''+2\rho P'+\lambda P}{\rho^2 P}+
\frac{\Lambda Y }{Y}=0$$
If not, equation (16) would not follow
$$\rho^2 P''+2\rho P'+(\lambda \rho^2  l(l+1) )P=0.$$

Indeed.

Minor typo at the end of Theorem 2
It should be $m=l,1l,\ldots,l1,l$ not $m=l,1l,\ldots,l1,m $